Influence of geometrical parameters of chisel on traction characteristics and resource of domestic ploughshares - D. A. Mironov; I. V. Liskin; S. A. Sidorov (Сельскохозяйственные машины и технологии)
A ploughshare is the most laden and fast-worn out detail of the arable unit. The authors developed and carried out operational tests of a new ploughshare with retracting face-mounted chisel. This tool meets all main European requirements for quality of soil tillage. A front surface of a ploughshare body has an evolvent form. As result, an angle of cutting edge decreases continuously in the direction from field to a slot part. Body and chisel edges are built up by a hard-facing alloy. A zone of a ploughshare nose part intended for deepening of the plow case has optimum value for plows of the types PLN-3…8-35. Parameters of middle back heel part allow to lower load of a ploughshare to the minimum traction resistance. The authors carried out field trials for determination of traction resistance depending on geometrical parameters of chisels, in particular from width and exposure of a chisel, and resource tests until a limit state on wear and breakages or in connection with the end of an arable season. Tests showed that on heavy soils with firm mechanical inclusions the resource of experimental ploughshares with a retracting face-mounted chisel exceeded a resource serial ones P702 with cutting edge welding by 3.0-3.5 times. The average operating time of experimental ploughshares was 3.0-3.5 times more than an operating time of serial ones. The effect from use of experimental ploughshares by criterion price-quality was 1.5-1.9 times higher than the serial ones.